Usefulness of induction chemotherapy followed by definitive chemoradiotherapy for oropharyngeal cancer: implications for the selection of candidates for organ-preserving treatment based on the response to induction chemotherapy - Yanagi, Takeshi; Shibamoto, Yuta; Murata, Rumi; Baba, Fumiya; Hashizume, Chisa; Nagai, Aiko; Miyakawa, Akifumi; Iwabuchi, Michio; Uchiyama, Kaoru; Sugie, Chikao (European Journal of Oncology and Environmental Health, 2015)
Background and aim of the work: This study aims to evaluate the usefulness of the response to induction chemotherapy (IC) in selecting candidates for definitive concurrent chemoradiotherapy in oropharyngeal cancer. Methods: Thirty-nine patients with oropharyngeal cancer received IC followed by definitive chemoradiotherapy or radiotherapy. The predominant IC regimens involved cisplatin and 5-fluorouracil with or without docetaxel. Patients who responded to IC received definitive organ-preserving treatment. Surgery was considered for patients who did not respond to IC. Only patients who underwent definitive radiotherapy were analyzed in this study. The associations between clinical parameters and local control (LC) or overall survival (OS) were also analyzed. Results: The follow-up periods of the surviving patients ranged from 9-170 months (median, 40). The 5-year LC and OS rates for all 39 patients were 81% and 60%, respectively. The 5-year LC and OS rates of the IC responders, complete response or partial response (CR, PR) were 89% and 65%, respectively, whereas those of the non-responders, stable disease or progressive disease (SD, PD) were 34% and 38%, respectively. Multivariate analysis demonstrated that the response to IC (p=0.00) and T-category (T1, 2 vs. T3, 4) (p=0.03) were correlated with LC, but only the response to IC was correlated with OS (p=0.04). None of the patients suffered severe late complications. Conclusions: Chemoselection appears to aid the selection of optimal treatments for patients with oropharyngeal cancer.